Весовые гири из пригородных усадеб ольвийской хоры VIV вв. до н. э. - Папанова, В.А.; Ляшко, С.Н. (Археологія і давня історія України, 2015)
В научный оборот вводятся весовые гири классического времени, раскопанные в последнее время на пригородных усадьбах Ольвии. Всего найдено семь весовых гирь V–IV вв. до н. э. Одна гиря
из камня/гальки и шесть свинцовых. Среди них
гири редкой формы: три в виде половины астрагала V в. до. н.э. и в виде овечьей/бычьей шкуры
V-IV вв. до. н.э. Автори відзначають вагомий внесок у вивчення
і розробку проблем античної метрології Північного
Причорномор’я Валентини Володимирівни Крапівіної. Основна кількість відомих за результатами
розкопок гир була знайдена на території Ольвії та
Березані. За весь час дослідження ольвійської хори
у ХХ ст. було знайдено лише чотири примірники
вагових гир на поселеннях Варварівка, Стара
Богданівка 2 і Сіверський Маяк, на Бейкушському поселенні. Розкопки останнього десятиліття
на ближній ольвійської хорі сприяли поповненню
джерельної бази вагових гир. Так, на приміських
садибах ближньої хори Ольвії знайдено сім вагових гир V–IV ст. до н. е. Одна гиря з каменю/гальки
і шість свинцевих. Гиря з невеликої світлої гальки
IV ст. до. н.е. На лицьовій стороні цієї гирі вирізані букви ΑΙλ(?)Ι(?). Вирізані на ній букви це або
клеймо ольвійських агрономів або знак власника.
Серед них три свинцеві гирі V ст. до. н.е. рідкісної форми у вигляді половини астрагалу. Вірогідно, що в Ольвії та на її хорі гирі у формі астрагалу використовувалися у другій половині
VI– V ст. до. н.е. Ще одна свинцева гиря рідкісної форми у вигляді овечої/бичачої шкури з сімома
пробитими отворами датується V–IV ст. до. н.е. Серед розглянутих гир відсутні контрольні гирі. Вага
гир варіює від 10 до 105 г. Всі вони відносяться до евбейсько-аттичної вагової системи. Аналогії їм
відомі з розкопок на Афінській агорі. Гирі представляють інтерес для уточнення низки питань
економічного життя Ольвійського поліса, зокрема для уточнення наявності або відсутності місцевих
вагових систем. Наданий матеріал не суперечить висновкам авторів розкопок двох приміських садиб
про розвинуті ринкові відносини серед населення
ольвійського поліса. Основним заняттям жителів садиб Широка балка 6 і Широка балка 7 було
сільське господарство з переважанням скотарства над землеробством. Ринкові відносини носили товарно-грошові відносини, про що свідчить велика кількість монет і вагові гирі, знайдені на обох садибах. Authors note a significant contribution to researching
and developing problems of Northern Black Sea
Coast’s ancient metrology by Valentina Vladimirovna
Krapivina. The basic amount of known by the results
of excavations weight dumbbells were found on the
territory of Olbia and Berezan. During total research
of Olbian chora in the twentieth century there were
found only four instances of weight dumbbells in the
settlements of Varvarovka, Staraya Bohdanovka 2
and Siversky Lighthouse on Beykushskom settlement.
Excavation of the last decade on the near Olbian
chora contributed to replenishment of weight dumbbells’
source base. So on suburban estates near Olbia
chora there were found seven weight dumbbells of
the Vth–IVth centuries BC. One dumbbell is of stone/
fine pebble and six dumbbells are of lead. The small
dumbbell of light-colored pebbles is the IVth century
BC. On the face of it letters ΑΙλ (?) Ι (?) are cut. Letter
λ (?])is inverted. Apparently carved letters are either
the brand of Olbian agronomists or the sign of owner.
Among them there are three lead dumbbells in a rare
form of half of Astragalus of the Vth century BC. Apparently,
in Olbia and its chora the dumbbells in the
form of Astragalus were used during the second half
of the VIth -Vth centuries BC. Another lead dumbbell
in a rare form of sheep / bovine skin with seven
punched holes is dated back to the Vth-IVth century
BC. Among the considered dumbbells there are no
control weight. The weight of dumbbells is ranging
from 10 to 105 g. All of them belong to the Euboea
Attic weight system. Their analogies are known from
excavations in the Athenian agora. Dumbbells are of
interest to clarify a number of issues of Olbian citystate’s
economic life, in particular to clarify the presence
or absence of local weight systems. The material presented here does not contradict the conclusions of
the authors of the excavation of two suburban estates on the development of market relations in the population
of Olbian city-state. The main occupation of the inhabitants of homesteads Shyroka Balka 6 and Shyroka
Balka 7 was agriculture with a predominance of cattle-breeding over arable farming. Market relations
were commodity-money relations, as evidenced by the number of coins and weight dumbbells found on both estates.